Discursive psychology as a method of analysis for the study of couple and family therapy. (8th March 2018) - O'Reilly, Michelle; Kiyimba, Nikki; Lester, Jessica N.
Abstract : The field of couple and family therapy has benefitted from evidence generated from qualitative approaches. Evidence developed from approaches relying on language and social interaction using naturally occurring recordings of real‐world practice has the benefit of facilitating practice‐based recommendations and informing practice. The aim of this article is to provide an overview of one approach to discourse analysis, Discursive Psychology (DP), demonstrating how a social constructionist framework and focus on discourse can provide an important contribution to the field of therapy. To illustrate the methodological decision‐making process for researchers and/or practitioners who utilize DP, we draw upon a video‐recorded therapeutic session involving Tom Andersen. To conclude, we make recommendations for practitioners using DP to explore and examine therapeutic practice.